2020
DOI: 10.1538/expanim.19-0153
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture alleviates Parkinson disease and regulates the expression of brain-gut peptides

Abstract: The non-motor symptoms (NMS) of Parkinson’s disease (PD) are found in more than 90% of patients with PD. Here, we explored the effects of electroacupuncture (EA) stimulation at Zhong wan (CV-12), Qihai (RN-7), Zusanli (ST-36) and Taichong (LR-3) on NMS and brain-gut peptides of PD. We found that EA intervention alleviated the motor deficit induced by 6-OHDA in rats indicated by the decreased abnormal involuntary movements (AIMs) scores and the net number of rotations and increased cylinder test grade. It also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…EA at CV12, Yinjiao (RN7), ST36, and LR3 suppresses glial cell activation, down-regulates TNF-α, IL-1β, COX-2, and other inflammatory factors in SN and ST, improving spatial memory function by rescuing dopamine neurons on the verge of apoptosis, which, in turn, partially restores motor function, and alleviates anxiety, depression, and other symptoms. 74 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…EA at CV12, Yinjiao (RN7), ST36, and LR3 suppresses glial cell activation, down-regulates TNF-α, IL-1β, COX-2, and other inflammatory factors in SN and ST, improving spatial memory function by rescuing dopamine neurons on the verge of apoptosis, which, in turn, partially restores motor function, and alleviates anxiety, depression, and other symptoms. 74 …”
Section: Resultsmentioning
confidence: 99%
“…Yu et al reported that EA treatment at CV12, Qihai (RN6), ST36, and LR3 alleviates Parkinson’s disease by regulating brain-gut peptides, such as, NPY, cholecystokinin, somatostatin, gastrin, and peptide YY. 74 In addition to nerve conduction, the brain-gut axis also includes the intestinal flora as well as the immune interactions in the brain-gut system. 166 Some studies have confirmed that the anti-inflammatory effect of acupuncture is related to its regulation of intestinal flora.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although peripheral nerves have a reconstitutive ability, it is difficult to fully recover nerve function after PNI. EA is not only effective in treating PNI [ 53 ] but can also be used for the treatment of neuropathic pain [ 54 ] and central nervous disease [ 55 ]. Since miRNAs are closely associated with the development of PNI [ 15 , 32 , 33 , 41 , 56 59 ] and nerve repair, while exosomes are valuable carriers of miRNAs [ 60 ], our study focused on exosomal delivery of miR-21 to explore the effects of EA.…”
Section: Discussionmentioning
confidence: 99%
“…However, such differential distribution and association were not found in white population (Goldman et al, 2004(Goldman et al, , 2011. Laboratory data showed that 6-OHDA treatment alone or together with L-DOPA treatment significantly increased the level of CCK or CCK-derived peptides in the SN (Taylor et al, 1992;Nilsson et al, 2009;Yu et al, 2020). Besides observatory study, some mechanism study might help understand the reasons behind the alteration of CCKs.…”
Section: Alterations In Intercellular Signaling Network Involving Dop...mentioning
confidence: 97%